PENGGUNAAN KONSENTRAT HIJAU DENGAN PROTEIN KASAR 16% TERHADAP KONSUMSI PAKAN DAN PERTAMBAHAN BOBOT BADAN PADA KAMBING PERANAKAN ETAWA - Platini, Pipin; Marhaeniyanto, Eko; Thiasari, Nurita (Universitas Tribhuwana Tunggadewi, 2016)
The aim of the study was to determine the effect of using green concentrate with crude protein content (CP) 16% using raw materials of Gliricidia maculata leaf flour, Leucaena leucochephala leaf flour, Caliandra calothyirsus leaf flour and Artocarpus heterophyllus leaf flour on feed intake and daily gain. The material used was 16 male Peranakan Etawa goats with an initial body weight of 29.41 ± 8.69 kg / head. The use of Gliricidia maculata leaf flour, Leucaena leucochephala leaf flour, Caliandra calothyirsus leaf flour and Artocarpus heterophyllus leaf flour with proportions (1: 1: 1: 1) in concentrates of 10%, 20% and 30%. Other constituent feed ingredients include milled corn, soybean meal, bran, minerals, salt, coconut cake, and molasses. The study used a randomized block design method (RBD) consisting of 4 treatments and 4 replications. P1 (basal feed + concentrate without addition of leaf flour), P2 (basal feed + green concentrate with 10% leaf flour), P3 (basal feed + green concentrate with 20% leaf flour), P4 (basal feed + green concentrate with 30% leaf flour), Basal feed given to goats during the study varied, namely Gliricidia maculata leaves, Leucaena leucochephala leaves, Tithonia diversifolia, Caliandra calothyirsus leaves, Chromolaena odorata, Manihot utilisima leaves, Ipomoea batatas leaves, Persea americana leaves, Artocarpus heterophyllus leaves, corn straw, Euphorbia hirta, field grass, and Cyanotis axillaris. The results showed the effect of green concentrate feed with a content of 16% CP and the addition of leaf flour as much as 30% in green concentrates, giving a significant effect (P